A morphologically transformable hypoxia-induced radical anion for tumor-specific photothermal therapy - Hongyu Wang; Dengyuan Hao; Qihang Wu; Tingting Sun; Zhigang Xie (Acta Pharmaceutica Sinica B)
Tumor microenvironment activatable therapeutic agents and their effective tumor accumulation are significant for selective tumor treatment. Herein, we provide an unadulterated nanomaterial combining the above advantages. We synthesize a perylene diimide (PDI) molecule substituted by glutamic acid (Glu), which can self-assemble into small spherical nanoparticles (PDI-SG) in aqueous solution. PDI-SG can not only be transformed into nanofibers at low pH conditions but also be reduced to PDI radical anion (PDI·‒), which exhibits strong near-infrared absorption and excellent photothermal performance. More importantly, PDI-SG can also be reduced to PDI·‒ in hypoxic tumors to ablate the tumors and minimize the damage to normal tissues. The morphological transformation from small nanoparticles to nanofibers makes for better tumor accumulation and retention. This work sheds light on the design of tumor microenvironment activatable therapeutics with precise structures for high-performance tumor therapy.